Examining Domestic Violence from The Lens of Islamic Law: A Maqasid Analysis - Ladiku, Hamdan; Zaman, Akhmad Roja Badrus (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2023)
This article aims to examine domestic violence from the perspective of Islamic law with a focus on the maqasid sharia. This study is important to present as a counter-narrative to the widespread view that Islam legalizes violence, due to the tradition of reading normative texts (the Qur'an and Hadith) in a textualist manner. This research uses a quasi-qualitative and descriptive approach and falls into the category of library research. In gathering data sources, the researcher used various instruments, such as observation and documentation or study of related documents. The primary data sources of this research are the Qur'an, Hadith, and fatwas of scholars, while the secondary data sources consist of other relevant literature such as books and journals related to the topic under study. The analysis used by the researcher includes data reduction, data display, and conclusion drawing. To clarify the validity of the data, the researcher conducted source and method triangulation. From the study conducted, this research concludes that Islamic teachings reject domestic violence and advocate for a humane and just approach within the framework of Islamic law. The prophetic tradition reinforces the prohibition against violence towards women based on the principle of mu’asyarah bi al-ma’ruf (living together in kindness) in Islam. This study encourages the goverment and related institutions to strengthen legal protection for victims and to enforce strict sanctions against perpetrators of violence.